The long flight home [large type] - Hlad, Alan (Center Point Large Print, 2019)
"It is September 1940-a year into the war-and as German bombs fall on Britain, fears grow of an impending invasion. Enemy fighter planes blacken the sky around the Epping Forest home of Susan Shepherd and her grandfather, Bertie. After losing her parents to influenza as a child, Susan found comfort in raising homing pigeons with Bertie. All her birds are extraordinary to Susan-loyal, intelligent, beautiful-but none more so than Duchess. Hatched from an egg that Susan incubated in a bowl under her grandfather's desk lamp, Duchess shares a special bond with Susan and an unusual curiosity about the human world. Thousands of miles away in Buxton, Maine, a young crop-duster pilot named Ollie Evans has decided to travel to Britain to join the Royal Air Force. His quest brings him to Epping and to the National Pigeon Service, where Susan is involved in a new, covert assignment. Codenamed Source Columba, the mission aims to air-drop hundreds of homing pigeons in German-occupied France. Many will not survive. Those that do make the journey home to England can convey crucial information on German troop movements-and help reclaim the skies from the Luftwaffe.The friendship between Ollie and Susan deepens as the mission date draws near. When Ollie's plane is downed behind enemy lines, both know how remote the chances of reunion must be. Yet Duchess's devotion and her singular sense of duty will become an unexpected lifeline, relaying messages between Susan and Ollie as war rages on-and proving, at last, that hope is never truly lost. "--Publisher.